Alternating electrical fields to stimulate osteogenic cells and biomimetic calcium phosphate-coated titanium substrates–A combinatorial approach to bone regeneration - Kreller, Thomas; Boccaccini, Aldo R.; Jonitz-Heincke, Anika; Detsch, Rainer (Biomaterials Advances, 2025)
Biophysical stimuli such as alternating electrical fields can mimic endogenous electrical potentials and currents in natural bone. This can help to improve the healing and reconstruction of bone tissue. However, little is known about the combined influence of biomaterials and alternating electric fields on bone cells. Therefore, this study aimed to investigate the impact of both, biomaterials and alternating electric fields, on osteoblast as well as osteoclast differentiation. Initially, either RAW 264.7 or MC3T3-E1 cells were seeded on Ti6Al4V substrates as a load-bearing implant material, modified with biomimetic calcium phosphate (BCP), or uncoated as a reference. The cells were stimulated towards osteoclastic and osteoblastic differentiation via respective growth factors. The effects of BCP substrate modification on cell differentiation were examined after 7 days for RAW 264.7 and after 14 days for MC3T3-E1 cells. In a further series of tests, either RAW 264.7 or MC3T3-E1 cells were seeded on BCP-modified Ti6Al4V substrates, stimulated towards differentiation using growth factors, and further electrically stimulated via alternating electric fields of different voltages and frequencies. In parallel to the first test series RAW 264.7 and MC3T3-E1 cells were stimulated for 7 and 14 days, respectively. Cell morphology was examined via scanning electron microscopy. Cell viabilities were assessed via WST-8 assay. Electrically stimulated MC3T3-E1 cell orientation was evaluated based on fluorescence microscopy images. Marker genes were examined via qPCR. While BCP increased osteoclast-specific gene expression, it had the opposite effect on osteoblast-related genes compared to respective cells seeded on uncoated Ti6Al4V substrates. ES with different parameters showed a broad cellular response due to electrocoupling. While cell viability assessments and gene expression analyses showed clear differences between ES samples and unstimulated controls, only minor cell morphology and orientation differences were observed. Furthermore, there was no clear trend towards a dominant influence of either voltage or frequency as control parameters. Further studies were initiated to investigate the underlying intracellular mechanisms targeted by ES. This work provides an introduction to the targeted control of cellular processes using defined electric fields. The optimization of voltage and frequency could provide therapeutic windows to control specific cellular functions and potentially improve bone regeneration and remodeling processes.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Biomaterials; Biomimetic calcium phosphate; Bone cells; Electrical stimulation

Alternating electric field stimulation: Phenotype analysis and osteoclast activity of differentiated RAW 264.7 macrophages on hydroxyapatite-coated Ti6Al4V surfaces and their crosstalk with MC3T3-E1 pre-osteoblasts - Kreller, Thomas; Zimmermann, J.; van Rienen, U.; Boccaccini, Aldo R.; Jonitz-Heincke, A.; Detsch, Rainer (Biomaterials Advances, 2023)
Biophysical stimuli can mimic endogenous electric potentials and currents in the natural bone to enhance tissue healing and reconstruction in diseased bone. However, little is known about the influence of electric fields on osteoclasts. Therefore, this study aimed to investigate the effects of alternating electric fields on osteoclast differentiation and activity. In this in vitro study, RAW 264.7 cells were seeded on Ti6Al4V substrates, as a loadbearing implant material modified with biomimetic calcium phosphate (BCP) and stimulated towards osteoclastic differentiation via growth factors. The effects of directly coupled alternating electric fields (0.7 Vrms, 20 Hz) on cell behavior were examined for up to 28 days. Alternating electric field simulation was performed using the finite element method. Changes in cell and substrate morphology were examined via light and fluorescence imaging. Cell viability was assessed via WST-8 assay. The effect of electrical stimulation (ES) on intercellular signaling and crosstalk was evaluated using indirect co-cultures with murine MC3T3-E1 pre-osteoblasts by qPCR. Morphological analysis proved the successful differentiation of macrophages into osteoclast-like cells for both electrically stimulated samples as well as unstimulated controls. ES promoted RAW 264.7 viability within the first seven days and induced a cellular response at gene expression levels. Gradually decreased expression rates of genes related to osteoclast differentiation and activity within 28 days could indicate a long-term inhibitory effect of ES on osteoclastogenesis and osteoclast activity while significantly upregulated carbonic anhydrase type 2 expressions could be a consequence of membrane depolarization to maintain intercellular pH levels. In this context, we were also able to demonstrate the degradation of the BCP surface by cellular influence. ES affected the crosstalk between osteoblast-, and osteoclast-like cells. Supernatants of electrically stimulated RAW 264.7 specimens led to decreased MC3T3-E1 viabilities and mineralization. While osteopontin expression in MC3T3-E1 cells was significantly decreased, markers of osteogenic differentiation showed higher expression rates. Underlying biophysical mechanisms in combination with biomaterials are part of ongoing research.
CRIS-Team Scopus Importer:2023-01-20
Keywords: Alternating electric fields; Electrical stimulation; Hydroxyapatite; Osteoclasts; RAW 264.7

Biomimetic calcium phosphate coatings for bioactivation of titanium implant surfaces: Methodological approach and in vitro evaluation of biocompatibility - Kreller, Thomas; Sahm, Franziska; Bader, Rainer; Boccaccini, Aldo R.; Jonitz-Heincke, Anika; Detsch, Rainer (Materials, 2021)
Ti6Al4V as a common implant material features good mechanical properties and corrosion resistance. However, untreated, it lacks bioactivity. In contrast, coatings with calcium phosphates (CaP) were shown to improve cell–material interactions in bone tissue engineering. Therefore, this work aimed to investigate how to tailor biomimetic CaP coatings on Ti6Al4V substrates using modified biomimetic calcium phosphate (BCP) coating solutions. Furthermore, the impact of substrate immersion in a 1 M alkaline CaCl2 solution (pH = 10) on subsequent CaP coating formation was examined. CaP coatings were characterized via scanning electron microscopy, x-ray diffraction, energy-dispersive x-ray spectroscopy, and laser-scanning microscope. Biocompatibility of coatings was carried out with primary human osteoblasts analyzing cell morphology, proliferation, collagen type 1, and interleukin 6 and 8 release. Results indicate a successful formation of low crystalline hydroxyapatite (HA) on top of every sample after immersion in each BCP coating solution after 14 days. Furthermore, HA coating promoted cell proliferation and reduced the concentration of interleukins compared to the uncoated surface, assuming increased biocompatibility.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Hydroxyapatite; Interleukins; Primary human osteoblasts; Ti6Al4V

Physico-chemical modification of gelatine for the improvement of 3D printability of oxidized alginate-gelatine hydrogels towards cartilage tissue engineering - Kreller, Thomas; Distler, Thomas; Heid, Susanne; Gerth, S.; Detsch, Rainer; Boccaccini, Aldo R. (Materials & Design, 2021)
This work explored 3D printing to mimic the intrinsic hierarchical structure of natural articular cartilage. Alginate di-aldehyde- gelatine (ADA-GEL) hydrogel was used as ink to create hierarchically ordered scaffolds. In comparison to previously reported ADA-GEL compositions, we introduce a modified formulation featuring increased amounts of thermally modified gelatine. Gelatine was degraded by hydrolysis which resulted in tailorable printability characteristics further substantiated by rheological analysis. ADA (3.75 %w/v)-GEL (7.5 %w/v) with gelatine modified at 80 °C for 3 h could be printed in hierarchical complex structures reaching scaffold heights of over 1 cm. The hierarchical structure of the scaffolds was confirmed via µCT analysis. To examine mechanical properties as well as the suitability of the hydrogel as a proper matrix for cell seeding and encapsulation, nanoindentation was performed. Elastic moduli in the range of 5 kPa were measured. Gelatine heat pre-treatment resulted in modifiable mechanical and rheological characteristics of ADA-GEL. In summary, this study demonstrates the possibility to enhance the printability of ADA-GEL hydrogels to fabricate hierarchical scaffold structures with shape stability and fidelity, without the necessity to change the initial hydrogel chemistry by the use of additives or crosslinkers, providing a valuable approach for fabrication of designed scaffolds for cartilage tissue engineering.
CRIS-Team Scopus Importer:2021-07-16
Keywords: 3D Printing; Gelatine; Hydrogels; Oxidized Alginate; Tissue Engineering